ANALISIS PENERAPAN E-FILING SEBAGAI UPAYA MENINGKATKAN KEPATUHAN WAJIB PAJAK DALAM PENYAMPAIANSURAT PEMBERITAHUAN (SPT) TAHUNANPADA KANTOR PELAYANAN PAJAK PRATAMAGRESIK UTARA - NIDYA ASTUTI, INNE (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTSPT is very important for the country to describe taxpayer compliance in the reporting of tax payments. To realize e-government in taxation, the directorate of taxes provides easiness of delivery an annual SPT via e-Filing, which is one of tax modernization. The implementation of e-Filing at service tax office Gresik Utara has been run in accordance with the procedure of e-Filing registration based on tax regulations. In addition, service tax office effort in the dissemination of e-Filing has a positive impact of improving tax compliance in the delivery of SPT. That is characterized by increased total of SPT which is received every year even though non comparable with total of taxpayer registered.Keywords: e-Filing, Tax Modernization, Taxpayer Compliance